Templated growth of oxcba: PFO-DBT nanostructures for humidity sensing application / Muhamad Saipul Fakir - Muhamad Saipul , Fakir (2018)
In recent years, research on the production of electronic devices has been emphasized to produce the electronic devices that have a simple production process are more cost effective and have better adaptation to the environment. In order to produce such devices, a variety of organic materials such as polymers and small molecules have been introduced. Therefore, one of the thiophene-based material, poly[2,7-(9,9- dioctylfluorene)-alt-4,7-bis(thiophen-2-yl)benzo-2,1,3-thiadiazole] (PFO-DBT) is used as the p-type semiconductor material while the fullerene-based material, o-xylenyl-C60- bisadduct (OXCBA) is used as n-type semiconductor material. Both of them have good optical properties and are suitable to be used as the active layer for the light-based device. However, its performance has been limited by the light absorption ability due to the structural nanoscale constraint. Introducing a nanostructure at the thin film enhanced the light absorption intensity and can solve the low absorption issue at the thin film. To overcome these limitations, fabrication of nanostructures such as nanotubes, nanorods and other novel nanostructures formation are rather essential and pragmatic. Therefore, the production of nanostructures has been carried out in this study. It was realized by the assistance of the anodic aluminium oxide (AAO) template. The resulting nanostructures were varied depending on the deposition technique. The first part of the research is to deposit the p-type material with different techniques. Solution deposition was done by the spin coating, immersing and vortex mixing methods. For the spin coating method, the type and size of nanostructure were varied by varying the solution concentration and spin rate, while for immersion method, parameters such as solution concentration, immersion time and type of solvent were varied. In the deposition by vortex mixer, the speed setting of the instrument was varied in order to get the different vibration strength, besides varying the solution concentration in order to achieve the same objective. Nanorods and nanotubes were successfully produced by the proposed methods. OXCBA was then deposited by spin coating method into the preformed PFO-DBT nanotubes. Infiltration of OXCBA into the hollow space of PFO-DBT nanotube was successfully done and led to the formation of core-shell OXCBA: PFO-DBT nanocomposite. The second part of this research has focused on the fabrication of the organic humidity sensor. The presence of a highly porous surface structure is one of the contributing factors for a better humidity sensor, which is the novelty of this research. With the high surface area of the structure, the performance of the sensors in term of their sensitivity, hysteresis value and response and recovery time for over a wide range of relative humidity level can be enhanced.